Fearfully and wonderfully made. - Yancey, Philip (Zondervan., 1980)
Mysterious, intricate, pulsing with energy...The human body is an endlessly fascinating repository of secrets. The miracle of the skin, the strength and structure of the bones, the dynamic balance of the muscles . . .your physical being is knit according to a pattern of incredible purpose. In Fearfully and Wonderfully Made, renowned surgeon Dr. Paul Brand and best-selling writer Philip Yancey explore the human body. Join them in a remarkable journey through inner space -- a spellbinding world of cells, systems, and chemistry that bears the impress of a still deeper, unseen reality. This Gold medallion Award-winning book uncovers eternal statements that God has made in the very structure of our bodies, presenting captivating insights into the Body of Christ.